PENGARUH KEPEMIMPINAN TERHADAP MOTIVASI DAN KINERJA PEGAWAI - Ayi Nasrudin (Tatar Pasundan : Jurnal Diklat Keagamaan, 2020)
This article intends to disclose the relationship between leadership and employee motivation with its performance. Theorizers’ generally agree that leaders have an important role in motivating employees. It turns out boosting their performance. By means of tracing and analying from the various related literature, it can be concluded that one's performance is heavily influenced by the presence of leaders who are able to give adequate appreciation to their accomplishment. It also becomes supreme motivation over the employees to continuously maintain and improve their performance over time.Keywords: Leadershi; Motivation; Performance